2023
DOI: 10.3390/nu15081818
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plasma 25(OH)D3 and Vitamin D Binding Protein Levels with COVID-19 Severity and Outcome in Hospitalized Patients

Abstract: Background: The Coronavirus Disease-19 (COVID-19) caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has been declared a worldwide pandemic. The severity of COVID-19 varies greatly across infected individuals. Possible factors may include plasma levels of 25(OH)D and vitamin D binding protein (DBP), as both are involved in the host immune response. Other possible nutrition-related factors include malnutrition and/or obesity which disrupt the optimal host immune response to infections. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Multiple studies have con rmed a signi cant correlation between VDBP gene polymorphism and COVID-19 [7][8][9][10][11][12], but there is no consistent conclusion between VDBP and the severity and mortality of COVID-19. Alabdullatif W. found that the VDBP of the critical COVID-19 was signi cantly higher than that of the non-critical group [13], which is consistent with our ndings. Povaliaeva A. also found that VDBP in COVID-19 patients was higher than in healthy people, but the correlation between VDBP and the severity was insigni cant [14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Multiple studies have con rmed a signi cant correlation between VDBP gene polymorphism and COVID-19 [7][8][9][10][11][12], but there is no consistent conclusion between VDBP and the severity and mortality of COVID-19. Alabdullatif W. found that the VDBP of the critical COVID-19 was signi cantly higher than that of the non-critical group [13], which is consistent with our ndings. Povaliaeva A. also found that VDBP in COVID-19 patients was higher than in healthy people, but the correlation between VDBP and the severity was insigni cant [14].…”
Section: Discussionsupporting
confidence: 90%
“…Vitamin D-binding protein (VDBP), which was well known as the primary carrier of vitamin D metabolites, was also found to be closely related to COVID-19 in recent research [7][8][9][10][11][12][13][14][15][16]. Previous studies discovered that VDBP not only plays a vital role in maintaining stable serum level of vitamin D and modulating its bioavailability but also play an essential role in the progress of in ammatory and immunoregulation functions independent of vitamin D carriage [17].…”
Section: Introductionmentioning
confidence: 99%